Meanings of Palliative Care for family members and its implications for anticipatory mourning - Cristine Gabrielle da Costa dos Reis; Carmen Leontina Ojeda Ocampo Moré; Marina Menezes; Estefânia Ibarra Dobes da Rosa; Raquel Campos (Revista de Psicología, 2022)
This qualitative study aimed to understand the meanings attributed to Palliative Care and its implications for the anticipatory mourning process, from the perspective of family caregivers. Participants were 14 family members of patients in Palliative Care. Participant observation and semi-structured interviews were carried out. The data were analyzed and organized based on the Grounded Theory, using the Atlas.ti 7.5 software. The results showed the meanings attributed to Palliative Care marked by the impact of the treatment proposal, by the emergence of feelings and experiences, and traversed by the specific care requirements, the treatment, and the decision making, generating repercussions in the caregiver’s life. Visualizing the set of meanings attributed during the process permits the support of actions in Palliative Care that recognize elements that constitute anticipatory mourning.